Management of Laboratories in General Education of Davao Doctors College - Dela Torre, Corazon T. (JPAIR Multidisciplinary Research, 2009)
This study was carried out to evaluate and assess the management of the General Education Laboratories of the Davao Doctors College. The study utilized the descriptive method of research. The study was conducted in the institution where the laboratories are located and used by the faculty and students. A total of fifty two (52) respondents (47 laboratory instructors and 5 staff) thru universal sampling answered the survey instrument. Compliance to the standards of PACUCOA and other regulatory agencies is notably high. The management of the laboratory in General Education is moderately Extensive and functioning very well and this must be sustained to maintain good operations and delivery of laboratory services.
Keywords: management of educations; institutional support; compliance